Strategi Pengembangan Pemasaran Gula Aren di Kabupaten Garut - Febrianti, Tintin; Azhari, Gishni Sahila (AGRITEKH (Jurnal Agribisnis dan Teknologi Pangan), 2025)
Garut Regency has great potential in developing palm derivative products, especially palm sugar, as a regional superior commodity. However, marketing this product still faces various obstacles such as limited market access, lack of innovation in marketing strategies, and minimal use of technology. This research aims to identify and develop marketing development strategies for palm sugar products in Garut Regency using SWOT analysis. The research was conducted in three main palm sugar producing sub-districts, namely Bungbulang, Cisewu, and Pakenjeng, with data collection techniques through field surveys, interviews, and Focus Group Discussions (FGD) using descriptive methods and using purposive sampling techniques involving 30 respondents from palm sugar farmers and craftsmen. SWOT analysis identifies strengths, weaknesses, opportunities and threats related to sugar marketing. The results of the analysis produced 11 alternative development strategies with the main strategies supported by commodity stakeholders including plant rejuvenation, product diversification, technology training, strengthening modan and developing export markets. The implementation of this strategy is expected to expand market reach, increase farmers' income, and encourage Garut Regency palm sugar products to compete in national and international markets. This research emphasizes the importance of collaboration between farmers, craftsmen, government and the private sector for the desire and optimization of palm sugar marketing.